2007
DOI: 10.1007/s10930-007-9111-2
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Four New Cysteine Endopeptidases From Fruits of Bromelia pinguin L. Grown in Cuba

Abstract: Bromelia pinguin L. is a plant broadly distributed in Central America and Caribbean islands. The fruits have been used in traditional medicine as anthelmintic, probably owed to the presence of a mixture of cysteine endopeptidases, initially termed pinguinain. This work deals with the purification and characterization of the four main components of that mixture, two of them showing acid pI and the other two alkaline pI. Molecular masses (SDS-PAGE and MALDI-TOF), N-terminal sequence and the reactivity and kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
4
9
0
3
Order By: Relevance
“…4B); this behavior may be due to the fact that DTT is a reducing agent of sulfhydryl groups, which is used to eliminate the disulfide bonds between one or more polypeptide chains. However, it is also known that at low concentrations, DTT protects the proteolytic activity of extracts of B. pinguin [23], because it favors the formation of sulfhydryl group (-SH), allowing the active site of the enzyme to be active. It is important to note that similar effects of DTT on B. karatas were observed in this study; one could consider that its proteases are also cysteine proteases.…”
Section: Discussionmentioning
confidence: 99%
“…4B); this behavior may be due to the fact that DTT is a reducing agent of sulfhydryl groups, which is used to eliminate the disulfide bonds between one or more polypeptide chains. However, it is also known that at low concentrations, DTT protects the proteolytic activity of extracts of B. pinguin [23], because it favors the formation of sulfhydryl group (-SH), allowing the active site of the enzyme to be active. It is important to note that similar effects of DTT on B. karatas were observed in this study; one could consider that its proteases are also cysteine proteases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the different genetic characteristics of each fruit species synthetize endopeptidases with different structure and catalytic activities (Headon and Walsh, 1994). B. karatas proteases had the lowest enzymatic activity; but the proteolytic activity was similar than purified B. pinguin proteases (7.11 to 11.0 U/mg protein) of fruits harvested in Cuba (Payrol et al, 2005(Payrol et al, , 2008.…”
Section: Proteolytic Activitymentioning
confidence: 99%
“…Sin embargo, hay que considerar aquí la presencia en B. pinguín de enzimas proteasas, en particular la pinguinaína, un pre parado enzimático con actividad proteolítica presente en el fruto de esta especie la cual ya ha sido blanco de diferentes estudios (27), (28), (29), (9), (30).…”
Section: Actividad Antifúngicaunclassified